2010
DOI: 10.1111/j.1524-4733.2010.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Child versus Parent Reports of the Child's Health-Related Quality of Life in Children with Epilepsy and Healthy Siblings

Abstract: Objectives Self-versus proxy- perspectives may produce different results that are important for clinical decision-making and for assessing outcomes in research studies. We examined differences in child versus parent-report of the child's health-related quality of life (HRQOL) in a large prospective, community-based study of newly diagnosed childhood epilepsy that included children with epilepsy (case) and sibling controls. Methods HRQOL was assessed 8–9 years after initial diagnosis of epilepsy in a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 43 publications
9
91
1
6
Order By: Relevance
“…A few studies have reported concordance between parent and child reports of child HRQL, 49,50 whereas others have documented discordance. [51][52][53] Furthermore, a recent study by Ferro (2014) identified informant as a moderator of associations between risk factors and child HRQL. 12 Correspondingly, to improve our understanding of robust risk factors of HRQL, future researchers should remain cognizant of the proxy problem and overcome its limitations through the implementation of multi-informant methodologic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported concordance between parent and child reports of child HRQL, 49,50 whereas others have documented discordance. [51][52][53] Furthermore, a recent study by Ferro (2014) identified informant as a moderator of associations between risk factors and child HRQL. 12 Correspondingly, to improve our understanding of robust risk factors of HRQL, future researchers should remain cognizant of the proxy problem and overcome its limitations through the implementation of multi-informant methodologic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In support of mothers as reporters, we previously reported encouraging results from this same sample that mothers' reports of children's HRQL were not affected by mothers' depressive symptoms. 33 Parent report has been found to be an adequate substitute for child report at the group level, as used here, 34 but a recent study of CWE 35 found that parents reported poorer HRQL than children themselves. Recognizing the importance of patient report, it is included in the subsequent follow-up of this cohort currently under way.…”
Section: Figure Mean Quality Of Life In Children With Epilepsy Questimentioning
confidence: 99%
“…8 In addition, numerous reviews and studies report caregiverchild discrepancies in QOL scores. [9][10][11][12][13] Before asking which variables best explain or predict QOL, we need first to ask children.…”
mentioning
confidence: 99%